Pre-clinical safety assessments of gadobutrol in diabetes-induced neuropathy: In vivo, in vitro and in silico studies - Bilgin, Batuhan; Hekim, Munevver Gizem; Adam, Muhammed; Bulut, Ferah; Orhan, Seval Ulku; Tekin, Suat; Ozcan, Mete (Elsevier Ireland Ltd, 2025)
Due to its vascular complications, patients with diabetes mellitus (DM) are exposed to gadobutrol in imaging. However, the safety concerns of gadobutrol to diabetes-induced neuropathy, a common complication of DM, remain unclear as a scientific gap. This study aimed to investigate the effects of gadobutrol on hypersensitivity in a streptozotocin (STZ)-induced diabetic neuropathy model in mice and its effects on cytotoxicity and genotoxicity in high glucose (HG)-induced neuropathy in dorsal root ganglion (DRG) neurons. Adult (6-8 weeks old) BALB/c male mice were intraperitoneally administered STZ (150 mg/kg) and hot plate, cold plate, von Frey, and rota rod tests were performed 21 days after blood glucose levels rose above 250 mg/dL (N = 40). Gadobutrol was administered intravenously. DRG neurons were isolated from neonatal Sprague-Dawley rats and HG (45 mmol/L) was administered. Subsequently, 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) and comet assay were performed on gadobutrol-treated and HG-exposed DRG neurons. Furthermore, molecular docking analysis was performed between gadobutrol and catalase (CAT). STZ + gadobutrol showed a statistically significant increase in sensitivity in hot plate, cold plate and von Frey assays compared to STZ (p = 0.0013, p = 0.0019 and p = 0.0189, respectively). HG + gadobutrol showed statistically significant increases in cytotoxicity and genotoxicity compared to HG. The binding affinity of gadobutrol to CAT was determined as 8.59 kcal/mol. The results of this study suggest for the first time that gadobutrol can exacerbate diabetes-induced neuropathy. Further clinical studies are needed to elucidate these results, which may pose a new safety concern for patients with diabetic neuropathy.
Keywords: Diabetic neuropathy; Gadobutrol; Dorsal root ganglion; Cytotoxicity; Genotoxicity; Hypersensitivity; Contrast agents